Influence of volume of sample processed on detection of Chlamydia trachomatis in urogenital samples by PCR. - Goessens, W H (1995)
In the present study, it was demonstrated that the sensitivity of the PCR for the detection of Chlamydia trachomatis is influenced by the volume of the clinical sample which is processed in the PCR. An adequate sensitivity for PCR was established by processing at least 4%, i.e., 80 microliters, of the clinical sample volume per PCR. By using this preparation procedure, 1,110 clinical samples were evaluated by PCR and by cell culture, and results were compared. After discordant analysis, cell culture resulted in a sensitivity of 79.1% and PCR resulted in a sensitivity of 92.7%. Furthermore, it was shown that treatment with antibiotics immediately resulted in negative cell culture results but that PCR could give positive results up to 2 weeks posttreatment.